SISTEMATIC LITERATUR RIVIEW: PENGARUH MEDIA VIDEO PADA PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Lutfi Andriyani Kutsiyah; Firstina Alyatul Khusna; Nova Nina Khoirina; Rani Setiawaty (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to systematically examine the impact of using video in teaching Indonesian language at the elementary school level. Learning aids, including videos, are important resources that facilitate teachers in expanding students' knowledge and supporting the achievement of learning objectives efficiently. In the context of teaching Indonesian language, videos can improve students' communication skills, both in oral and written forms, and can increase appreciation for literary works. This study describes the influence of video media on learning Indonesian language in elementary schools based on the Systematic Literature Review (SLR). The use of video media can be used as an effective medium in learning activities. Learning that uses video media can be used as a reference for learning, and can improve student learning outcomes in boring learning.